Local Instructional Theory Topik Dua Tipe Kesalahan dalam Pengujian Hipotesis - Syafriandi Syafriandi; Ahmad Fauzan; Lufri Lufri; Armiati Armiati (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
Two types of errors are one of the important topics in hypothesis testing. Studying the two types of errors is not only studying how the procedure determines the probability of making an error, but it is very important to study the theoretical concepts of the two types of errors. To achieve this goal, a learning design is needed that can facilitate students to construct their own concepts of the two types of errors. The learning design developed is local instructional theory resulting from the cyclic process of hypothetical learning trajectory. The type of research used is design research using the model developed by Gravemeijer and Cobb. The test subjects used in this study were students of the Ma thematics Education Study Program, FMIPA UNP who took the Elementary Statistics Course in the July – December 2019 semester. This research resulted in a very practical local instructional theory used to facilitate students in carrying out horizontal and vertical mathematization processes, so that students are able to construct their own concepts of two types of errors in hypothesis testing.